PERAN SAKSI AHLI TERHADAP PENYELESAIAN TINDAK PIDANA PENYEROBOTAN LAHAN DALAM KAWASAN HUTAN LINDUNG DI NAGARI GURUN KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Arif, Zainal; Yustrisia, Lola; Zulfiko, Riki (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: Forestry crime cases in their settlement require expert testimony to provide an explanation of the rules that apply to the management of Protected Forest Areas. This research aims to determine the role of expert witnesses and to find out the obstacles faced by expert witnesses and efforts to overcome the obstacles faced by experts in providing testimony as expert witnesses in the settlement of criminal acts of land grabbing in protected forest areas in Nagari Gurun, Harau District, Lima Puluh Kota District. The results of the research explain that the role of expert witnesses is very important in the trial process, expert witnesses provide information that helps the course of the trial to be clear and bright. Evidence of expert testimony is placed in second place as systematized in Pasal 184 KUHAP. Obstacles as an expert witness in trials or investigative activities, namely 1) Expert witnesses are appointed based on their inherent position not on the specific expertise they have, 2) Lack of competence development activities for ASN in the field of special expertise in forestry and 3) Limited number of Forestry PPNS. Efforts that can be made include 1) Appointing expert witnesses who have certified expertise and knowledge, 2) Holding ASN competency development activities specifically on technical activities in Forestry and 3) Holding PPNS Formation Training.Keywords: Expert Witness, Crime, Forestry.